If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(h + 1.4) = 11(5 + -1h) Reorder the terms: 3(1.4 + h) = 11(5 + -1h) (1.4 * 3 + h * 3) = 11(5 + -1h) (4.2 + 3h) = 11(5 + -1h) 4.2 + 3h = (5 * 11 + -1h * 11) 4.2 + 3h = (55 + -11h) Solving 4.2 + 3h = 55 + -11h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '11h' to each side of the equation. 4.2 + 3h + 11h = 55 + -11h + 11h Combine like terms: 3h + 11h = 14h 4.2 + 14h = 55 + -11h + 11h Combine like terms: -11h + 11h = 0 4.2 + 14h = 55 + 0 4.2 + 14h = 55 Add '-4.2' to each side of the equation. 4.2 + -4.2 + 14h = 55 + -4.2 Combine like terms: 4.2 + -4.2 = 0.0 0.0 + 14h = 55 + -4.2 14h = 55 + -4.2 Combine like terms: 55 + -4.2 = 50.8 14h = 50.8 Divide each side by '14'. h = 3.628571429 Simplifying h = 3.628571429
| -2(4+2w)=6(w-10) | | -5(16.5+3t)=3(0.9-t) | | -5(16.5+32)=3(0.9-t) | | 5(16.5+32)=3(0.9-t) | | 5n+4=14 | | X+2x+x+8=52 | | 80c^3+52c^2-60=0 | | 7x-10=3x+66 | | 0=x^2+2x-35 | | 5a+10=6a-30 | | 12x^3-48X^2+18=0 | | 138+8y=4(3y+58) | | 4z+20=12 | | 22b^2-38b-12=0 | | 2x+17=5x-40 | | 6x+2(x+7)=49 | | 9a+a-8=20-4+2a | | 2x+7=65 | | X^2-2x-18=0 | | 5x-4=2x-10 | | 3s+s-6=14 | | 2x-7=65 | | -5x^2+13x-6=0 | | 7-44x+3=x-16-3x | | x/5+8=3 | | -3p+8=6-(6p+5) | | 1.08(1.28)(8-x)=10 | | -16x^2-32x+48=0 | | 2-3(x-4)=17 | | 3x+(-1)=-10+2x | | 0.3y-12=-2 | | 5(2c-8)=35c-5c |